DOA estimation with a vector circular array - Sun, Huaxi. (2013)
Circular array antennas are widely used in direction of arrival estimation (DOA) estimation applications in navigation and signal intelligence. Conventional scalar circular array (SCA) is limited to DOA estimation of low grazing angle incident signals with mainly vertically polarized signals. In this paper, we present a vector circular array (VCA) concept for DOA and polarization estimations of signals with relatively high grazing angle and arbitrary polarization.